Prediksi dan Validasi Porositas Kipas Aluminium Hasil Pengecoran Dengan Simulasi dan Eksperimen Berbasis Finite Difference Method - Dedhy Prihtiantoro; Agus Lutanto (P3M Politeknik Negeri Cilacap, 2025)
Porosity is a common defect in the aluminum casting process, particularly in thin-walled components such as compressor fans. This study aims to predict and validate porosity in cast aluminum fan components using a combined simulation and experimental approach. The simulation was conducted using the Finite Difference Method (FDM) with the aid of SOLIDCast and FLOWCast software to evaluate molten metal distribution, Niyama criterion, and solidification time. The experimental casting was carried out using silica sand molds and Aluminum A319 alloy, followed by metallographic analysis under an optical microscope. The results show a strong correlation between the simulation predictions and experimental findings, especially in the identification of microporosity, gas porosity, and localized shrinkage. This approach has proven effective in improving casting quality and can serve as a reference for optimizing gating system design.